Peak oxygen uptake correlates with indices of sarcopenia, frailty, and cachexia in older Japanese outpatients. Issue 2 (24th June 2021) - Sugie, Masamitsu; Harada, Kazumasa; Takahashi, Tetsuya; Nara, Marina; Fujimoto, Hajime; Kyo, Shunei; Ito, Hideki
Abstract: Background: Peak oxygen uptake (peak VO2 ) is known not only as an index of aerobic fitness but also one of an index of life expectancy. Frailty, sarcopenia, and cachexia are associated with a poor prognosis and high mortality. The purpose of this study was to determine the relationships of peak VO2 with the features of sarcopenia, frailty, and cachexia, to provide insight into which might mediate the poor prognosis. Methods: The first group of participants was 175 community‐dwelling older Japanese outpatients (58 men and 117 women; mean age 77.6 ± 6.4 years), in whom we assessed the features of sarcopenia, frailty, and cachexia, and measured peak VO2 during cardiopulmonary exercise. To confirm the relationships, we analysed another group of 162 participants (77.3 ± 5.5 years). Results: There were significant correlations between peak VO2 and the features of sarcopenia, frailty, and cachexia, with the exception of high sensitivity C‐reactive protein. Multiple linear regression analysis for the prediction of peak VO2 (mL/min) identified following formula: predicted peak VO2  = −11.6 × age (years) + 25.5 × haemoglobin concentration (g/dL) + 114.2 × skeletal muscle mass index (kg/m 2 ) + 8.9 × hand grip strength (kg) + 226.4 × usual walking speed (m/s) − 65.8 × fatiguability (absence 0, presence 1) − 177.4 × chronic heart failure (absence 0, presence 1) + 437.1 ( R 2  = 0.627, P  < 0.001). The validity of the formula was confirmed with another group ( r  = 0.78, P  < 0.001). Conclusions: This study has identified the features of sarcopenia, frailty, and cachexia that are related to peak VO2 in an older population.